Conductive adhesive and preparation method thereof, negative plate and battery
By using conductive adhesives with acrylic units and aniline units in the negative electrode sheet of the battery, and combining with the gradient distribution of the negative electrode active layer design, the problem of high internal resistance of the battery in the prior art is solved, and the battery is efficient fast charging and good battery life is achieved.
Patent Information
- Application Number
- CN202411817092.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-25
AI Technical Summary
When the prior art improves the battery fast charging capacity and endurance, it is difficult to reduce the battery internal resistance without reducing the content of the active substance of the pole sheet.
A conductive adhesive is used, and its structure includes acrylic units and aniline units, with a molar ratio of (1-4): 1, and is prepared by copolymerization reaction, for designing an anode active layer with a gradient distribution in the negative electrode sheet of a battery.
On the basis of not reducing the content of active substances on the electrode sheet, the internal resistance of the battery is reduced, the electrochemical reaction performance of the battery is improved, and the battery life is guaranteed.
Smart Images

Figure BDA0005182473530000011 
Figure BDA0005182473530000041 
Figure BDA0005182473530000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a conductive adhesive and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] With the rapid development of new energy vehicles, the market currently has higher requirements for the fast charging capability and endurance of new energy vehicles. In order to improve the fast charging capability of the battery and shorten the charging time, it is usually necessary to reduce the internal resistance of the battery so that the battery can meet the requirements of high-power charging.
[0003] In the related technology, the internal resistance of the battery is usually reduced by increasing the proportion of conductive agent in the electrode. However, since the conductive agent itself cannot contribute to the capacity during the battery charging and discharging process, as the proportion of conductive agent increases, the proportion of active material in the electrode will decrease accordingly, which will lead to a decrease in the capacity of the battery and a decrease in the battery's endurance. Summary of the invention
[0004] The embodiments of the present application provide a conductive adhesive that can reduce the internal resistance of the battery and improve the electrochemical reaction performance of the battery while ensuring the battery capacity.
[0005] In a first aspect, an embodiment of the present application provides a conductive adhesive, the structural formula of the conductive adhesive is shown in formula (1):
[0006]
[0007] Among them, m:n=(1-4):1.
[0008] In some embodiments, the molecular weight of the conductive adhesive is 0.9×10 6 -1.5×10 6 .
[0009] In a second aspect, an embodiment of the present application provides a method for preparing a conductive adhesive, which is used to prepare the conductive adhesive as described above, comprising:
[0010] The conductive adhesive is obtained by copolymerizing acrylic acid and aniline;
[0011] Wherein, the molar ratio of acrylic acid to aniline is (1-4):1.
[0012] In some embodiments, a method for preparing a conductive adhesive includes:
[0013] dispersing acrylic acid in a first solvent to obtain an acrylic acid solution;
[0014] Adding a first polymerization agent to an acrylic acid solution to obtain a first mixed solution, and subjecting the first mixed solution to a polymerization reaction to obtain a polyacrylic acid solution;
[0015] Adding sodium hydroxide solution to the polyacrylic acid solution, then adding aniline and a second polymerization agent to obtain a second mixed solution, subjecting the second mixed solution to a polymerization reaction to obtain a copolymer solution;
[0016] The copolymer solution is dried to obtain a conductive adhesive.
[0017] In some embodiments, dispersing acrylic acid in a first solvent to obtain an acrylic acid solution comprises:
[0018] Under a protective atmosphere, mixing acrylic acid and deionized water at a temperature of 30° C. to 40° C. to obtain an acrylic acid solution;
[0019] Wherein, the mass percentage of acrylic acid in the acrylic acid solution is 10%-15%.
[0020] In some embodiments, a first polymerization agent is added to an acrylic acid solution to obtain a first mixed solution, comprising:
[0021] adding ammonium persulfate and tetramethyldiethylamine to the acrylic acid solution to obtain a first mixed solution;
[0022] Wherein, in the first mixed solution, the mass ratio of acrylic acid, ammonium persulfate and tetramethyldiethylamine is (100-120):(1-1.2):(0.5-1.5).
[0023] In some embodiments, sodium hydroxide solution is added to the polyacrylic acid solution, and then aniline and a second polymerization agent are added to obtain a second mixed solution, and the second mixed solution is subjected to a polymerization reaction, comprising:
[0024] Add sodium hydroxide solution to the polyacrylic acid solution, and then add aniline and ammonium persulfate at 0°C-5°C;
[0025] The second mixed solution is reacted at a temperature of 0°C-5°C for 5h-12h.
[0026] In some embodiments, the molar ratio of aniline to the second polymerization agent is (0.5-2):1;
[0027] And / or, the molar ratio of sodium hydroxide to acrylic acid is (0.2-0.5):1.
[0028] In a third aspect, an embodiment of the present application further provides a negative electrode sheet, comprising a current collector, and a negative electrode active layer formed on at least one side of the current collector, wherein the negative electrode active layer comprises a negative electrode active material, a conductive agent, and a binder;
[0029] Wherein, the adhesive includes the conductive adhesive as described above, and / or the conductive adhesive prepared by the preparation method of the conductive adhesive as described above.
[0030] In some embodiments, the negative electrode active layer includes a first active layer and a second active layer, the first active layer is disposed on at least one side of the current collector, the second active layer is disposed on a side of the first active layer away from the current collector, the first active layer includes a conductive adhesive, and the second active layer includes a conductive adhesive;
[0031] The mass proportion of the conductive agent in the first active layer is a1, the mass proportion of the conductive agent in the second active layer is a2, and a1>a2;
[0032] In the conductive adhesive in the first active layer, n / m=b1, and in the conductive adhesive in the second active layer, n / m=b2, and b1<b2.
[0033] In some embodiments, 0.4%≤a1≤0.6%; and / or, 0.2%≤a2≤0.4.
[0034] In some embodiments, 0.25≤b1≤0.5; and / or, 0.7≤b2≤1.
[0035] In a fourth aspect, an embodiment of the present application further provides a battery, comprising the negative electrode sheet as described above.
[0036] Beneficial effects of the embodiments of the present application:
[0037] In the embodiment of the present application, the structural formula of the conductive adhesive is shown in formula (1), that is, the conductive adhesive includes acrylic acid units and aniline units, and the molar ratio of acrylic acid units to aniline units is (1-4): 1. The conductive adhesive provided in the embodiment of the present application can take into account both good bonding performance and conductive performance. By applying the conductive adhesive to the battery, the electrochemical reaction power of the battery can be increased without reducing the active material content in the electrode and affecting the battery capacity, thereby ensuring the battery life. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0039] In a first aspect, an embodiment of the present application provides a conductive adhesive, the structural formula of the conductive adhesive is shown in formula (1):
[0040]
[0041] Among them, m:n=(1-4):1.
[0042] In the embodiment of the present application, the structural formula of the conductive adhesive is shown in formula (1), that is, the conductive adhesive includes acrylic acid units and aniline units, and the molar ratio of acrylic acid units to aniline units is (1-4): 1. The conductive adhesive provided in the embodiment of the present application can take into account both good bonding performance and conductive performance. By applying the conductive adhesive to the battery, the electrochemical reaction power of the battery can be increased without reducing the active material content in the electrode and affecting the battery capacity, thereby ensuring the battery life.
[0043] In the conductive adhesive provided in the embodiment of the present application, there is a carboxyl group in the acrylic acid unit, which can form a strong hydrogen bond with the active material containing groups such as hydroxyl groups on the surface, thereby providing bonding performance. There is a strong binding force between the active material and the current collector. There are a large number of conjugated structures and nitrogen atoms in the aniline unit, which makes it have good conductivity. By reasonably setting the molar ratio between the acrylic acid unit and the aniline unit in the conductive adhesive, the conductive adhesive can have both good bonding and conductive properties. When the conductive adhesive provided in the embodiment of the present application is applied to a battery, since it has both bonding and conductive properties, after replacing the conventional adhesive, it can improve the electrochemical reaction power of the battery without increasing the content of the conductive agent, thereby reducing the internal resistance of the battery while ensuring the battery's endurance.
[0044] Illustratively, m:n may be 1:1, 1:2, 1:3 or 1:4.
[0045] It is understandable that the conductive adhesive provided in the embodiment of the present application may also use other polymer units with adhesive properties to replace the acrylic acid unit, such as acrylonitrile units, vinylidene fluoride units, etc., and may also use other polymer units with conductive properties to replace the aniline unit, such as pyrrole units, thiophene units, carbazole units, acetylene units, etc. In addition, the acrylic acid unit and the aniline unit in the embodiment of the present application may also be replaced.
[0046] In some embodiments, the molecular weight of the conductive adhesive is 0.9×10 6 -1.5×10 6 By setting the molecular weight of the conductive adhesive within the above range, it is possible to ensure that the conductive adhesive has a certain degree of polymerization, so that the conductive adhesive has good bonding and conductive properties. At the same time, the conductive adhesive can maintain good solubility, reduce process difficulty, and ensure coating uniformity.
[0047] For example, the molecular weight of the conductive adhesive may be 0.9×10 6 , 1.0×10 6 , 1.1×10 6 , 1.2×10 6 , 1.3×10 6 , 1.4×10 6 or 1.5 × 10 6 .
[0048] In a second aspect, an embodiment of the present application provides a method for preparing a conductive adhesive, which is used to prepare the conductive adhesive as described above, comprising:
[0049] Acrylic acid and aniline are copolymerized to obtain a conductive adhesive, wherein the molar ratio of acrylic acid to aniline is (1-4):1.
[0050] By copolymerizing acrylic acid and aniline, acrylic acid can be polymerized to form polyacrylic acid units, and aniline can be polymerized to form polyaniline units, so that the obtained conductive adhesive has both adhesive properties and conductive properties. By setting the molar ratio of acrylic acid to (1-4):1, the prepared conductive adhesive can ensure good adhesive properties and conductive properties at the same time. When it is applied to batteries, it can increase the electrochemical reaction power of the battery without increasing the conductive agent content and affecting the battery capacity, thereby ensuring the battery's endurance.
[0051] In some embodiments, a method for preparing a conductive adhesive includes: dispersing acrylic acid in a first solvent to obtain an acrylic acid solution;
[0052] Adding a first polymerization agent to an acrylic acid solution to obtain a first mixed solution, and subjecting the first mixed solution to a polymerization reaction to obtain a polyacrylic acid solution;
[0053] Adding sodium hydroxide solution to the polyacrylic acid solution, then adding aniline solution and a second polymerization agent solution to obtain a second mixed solution, subjecting the second mixed solution to a polymerization reaction to obtain a copolymer solution;
[0054] drying the copolymer solution to obtain a conductive adhesive;
[0055] Wherein, the molar ratio of acrylic acid to aniline is (1-4):1.
[0056] That is, acrylic acid and a first polymerizing agent are polymerized to form a polyacrylic acid solution, and then an aniline solution and a second polymerizing agent solution are added to the polyacrylic acid solution to cause a copolymerization reaction, and then a conductive adhesive is obtained by drying.
[0057] In some embodiments, dispersing acrylic acid in a first solvent to obtain an acrylic acid solution comprises:
[0058] Under a protective atmosphere, mixing acrylic acid and deionized water at a temperature of 30° C. to 40° C. to obtain an acrylic acid solution;
[0059] Wherein, the mass percentage of acrylic acid in the acrylic acid solution is 10%-15%.
[0060] At 30°C-40°C, acrylic acid and deionized water can form an acrylic acid solution with good stability, which is conducive to the smooth progress of subsequent reactions. By controlling the mass percentage of acrylic acid in the acrylic acid solution within the range of 10%-15%, the polymerization reaction of acrylic acid can be carried out under relatively mild conditions, and the yield of polyacrylic acid can be guaranteed, and the uniformity of molecular weight distribution and performance stability can be improved.
[0061] Illustratively, acrylic acid and deionized water may be mixed at 30° C., 32° C., 35° C., 37° C. or 40° C. In the acrylic acid solution, the mass percentage of acrylic acid may be 10%, 11%, 12%, 13%, 14% or 15%.
[0062] In some embodiments, a first polymerization agent is added to an acrylic acid solution to obtain a first mixed solution, comprising:
[0063] adding ammonium persulfate and tetramethyldiethylamine to the acrylic acid solution to obtain a first mixed solution;
[0064] Wherein, in the first mixed solution, the mass ratio of acrylic acid, ammonium persulfate and tetramethyldiethylamine is (100-120):(1-1.2):(0.5-1.5).
[0065] Ammonium persulfate is a strong oxidant that can accelerate the oxidation of acrylic acid, thereby initiating the polymerization of acrylic acid to form polyacrylic acid. Tetramethyldiethylamine (TEMED) can catalyze ammonium persulfate to produce free radicals, thereby accelerating the polymerization reaction of acrylic acid.
[0066] By setting the mass ratio of acrylic acid, ammonium persulfate and tetramethyldiethylamine to (100-120):(1-1.2):(0.5-1.5), the polymerization reaction of acrylic acid can be effectively initiated, and an appropriate polymerization speed can be ensured, so that the polymerization reaction can be carried out smoothly and efficiently, and the molecular weight distribution of the polymer can be uniform, thereby obtaining stable polyacrylic acid.
[0067] Illustratively, in the first mixed liquid, the mass ratio of acrylic acid, ammonium persulfate and tetramethyldiethylamine can be 100:1:0.5, 110:1.1:1, 100:1.2:1.5, 110:1:0.5, 110:1.1:0.5 or 100:1:1.5.
[0068] In some embodiments, the polymerization reaction time of the first mixed solution is 20-30 hours.
[0069] Illustratively, the polymerization reaction time of the first mixed solution can be 20 h, 22 h, 25 h, 27 h or 30 h.
[0070] In some embodiments, sodium hydroxide solution is added to the polyacrylic acid solution, and then aniline and a second polymerization agent are added to obtain a second mixed solution, and the second mixed solution is subjected to a polymerization reaction, comprising:
[0071] Add sodium hydroxide solution to the polyacrylic acid solution, and then add aniline and ammonium persulfate at 0°C-5°C;
[0072] The second mixed solution is reacted at a temperature of 0°C-5°C for 5h-12h.
[0073] By adding sodium hydroxide solution to the polyacrylic acid solution, the acidic carboxyl groups in the polyacrylic acid can be neutralized by sodium hydroxide, and the pH value of the solution can be adjusted, thereby providing a suitable environment for the subsequent aniline polymerization. Under the condition of 0℃-5℃, ammonium persulfate can induce the oxidative coupling reaction of aniline. The lower reaction temperature condition helps to reduce the occurrence of side reactions, ensure the purity of the product and the reaction stability, and make the reaction process more controllable.
[0074] For example, the temperature condition may be 0° C., 1° C., 2° C., 3° C., 4° C. or 5° C. The reaction time may be 5 h, 7 h, 9 h, 10 h or 12 h.
[0075] In some embodiments, the molar ratio of aniline to the second polymerization agent is (0.5-2):1.
[0076] That is, the molar ratio of aniline to ammonium persulfate is (0.5-2):1, which can make the reaction rate controllable, maintain a high reaction efficiency, and make the reaction more stable. In addition, by setting the ratio of the two within the above range, the product can meet the requirements and have good performance.
[0077] Illustratively, the molar ratio of aniline to the second polymerization agent may be 0.5:1, 1:1, 1.5:1, or 2:1.
[0078] In some embodiments, the molar ratio of sodium hydroxide to acrylic acid is (0.2-0.5): 1. By controlling the molar ratio of sodium hydroxide to acrylic acid, the pH value of the solution can be controlled within a suitable range, providing a suitable environment for subsequent reactions.
[0079] Illustratively, the molar ratio of sodium hydroxide to acrylic acid may be 0.5:1, 0.3:1, 0.4:1, or 0.5:1.
[0080] In a third aspect, an embodiment of the present application further provides a negative electrode sheet, comprising a current collector, and a negative electrode active layer formed on at least one side of the current collector, wherein the negative electrode active layer comprises a negative electrode active material, a conductive agent, and an adhesive. The adhesive comprises the conductive adhesive as described above, and / or a conductive adhesive prepared by the method for preparing the conductive adhesive as described above.
[0081] In the negative electrode sheet provided in the embodiment of the present application, the adhesive includes at least a portion of a conductive adhesive, so that the electrochemical reaction power of the battery can be improved without increasing the content of the conductive agent, thereby reducing the internal resistance of the battery while ensuring the battery life.
[0082] In some embodiments, the negative electrode active layer includes a first active layer and a second active layer, the first active layer is disposed on at least one side of the current collector, the second active layer is disposed on the side of the first active layer away from the current collector, the first active layer includes a conductive adhesive, and the second active layer includes a conductive adhesive. The mass proportion of the conductive agent in the first active layer is a1, the mass proportion of the conductive agent in the second active layer is a2, and a1>a2.
[0083] In the conductive adhesive in the first active layer, n / m=b1, and in the conductive adhesive in the second active layer, n / m=b2, and b1<b2.
[0084] Conductive agents usually have a large specific surface area and are prone to side reactions with the electrolyte, which in turn leads to a decrease in the cycle and storage performance of the battery. In the embodiment of the present application, the first active layer is arranged close to the current collector, and the second active layer is arranged on the side of the first active layer away from the current collector, that is, the first active layer is located on the inside and is not in direct contact with the electrolyte, and the second active layer is located on the outside and can be in direct contact with the electrolyte. By adopting a gradient distribution setting, the content of the conductive agent in the second active layer located on the outside is lower, reducing the side reaction of the conductive agent with the electrolyte. In order to reduce the impedance difference and uneven current distribution caused by the inconsistent content of the conductive agent in the first active layer and the second active layer, the first active layer and the second active layer respectively use conductive adhesives with different n / m. Due to the different molar ratios of aniline units and acrylic acid units in the conductive adhesive in the first active layer and the conductive adhesive in the second active layer, the conductive properties of the two are different. Among them, n / m=b1 in the conductive adhesive in the first active layer, n / m=b2 in the conductive adhesive in the second active layer, b1<b2. Since the proportion of aniline units in the conductive adhesive in the second active layer is higher and the conductive performance is better, the problem of low conductive agent content in the second active layer is compensated, making the conductive performance of the first active layer and the second active layer basically the same.
[0085] In some embodiments, 0.4%≤a1≤0.6%. By controlling the mass proportion of the conductive agent in the first active layer to be between 0.4% and 0.6%, a good conductive network can be formed in the first active layer, which has good dispersion performance and ensures the energy density of the first active layer.
[0086] Illustratively, a1 may be 0.4%, 0.5% or 0.6%.
[0087] In some embodiments, 0.2%≤a2≤0.4. Similarly, by controlling the mass proportion of the conductive agent in the second active layer to 0.2% to 0.4%, a good conductive network can be formed in the second active layer, with good dispersion performance, and the energy density of the second active layer can be guaranteed.
[0088] In addition, conductive adhesives are added to both the first active layer and the second active layer, which can improve the conductivity without increasing the content of the conductive agent. The decrease in conductivity caused by the low content of the conductive agent in the second active layer can be compensated by a conductive adhesive with better conductivity, thereby keeping the conductivity of the first active layer and the second active layer basically the same.
[0089] Illustratively, a2 may be 0.2%, 0.3% or 0.4%.
[0090] In some embodiments, 0.25≤b1≤0.5. By controlling b1 within the range of 0.25 to 0.5, that is, the molar ratio of aniline units to acrylic acid units in the conductive adhesive in the first active layer is 0.25-0.5, the conductive adhesive in the first active layer can have a certain conductivity while maintaining good adhesion. Since the first active layer is located on the inner side, the proportion of the conductive agent added is relatively high, and b1 is controlled within the range of 0.25 to 0.5 to meet the conductivity, while improving the adhesion, so that the first active layer can be better bonded to the surface of the current collector.
[0091] Illustratively, b1 may be 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5.
[0092] In some embodiments, 0.7≤b2≤1. By controlling b1 within the range of 0.25 to 0.5, that is, the molar ratio of aniline units to acrylic acid units in the conductive adhesive in the second active layer is 0.7-1, the conductive adhesive in the second active layer can have a certain conductivity while maintaining good bonding performance. Since the second active layer is located on the outside, the proportion of the conductive agent added is relatively low, and b2 is controlled within the range of 0.7 to 1, it can ensure that the second active layer is bonded to the first active layer while making the conductive properties of the second active layer and the first active layer basically consistent, reducing the impedance difference between the first active layer and the second active layer due to the inconsistent content of the conductive agent, and making the current more evenly distributed in the first active layer and the second active layer.
[0093] Illustratively, b2 may be 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 1.
[0094] In some embodiments, the conductive agent includes at least one of carbon black, carbon fiber, carbon nanotubes and superconducting carbon black. Carbon black has a large specific surface area and porosity, which helps to form a good conductive network and improve conductivity. Carbon fiber has high conductivity, good mechanical properties and high temperature and corrosion resistance. Carbon nanotubes have excellent conductivity and double layer effect, which helps to improve the high-rate charge and discharge performance of the battery. Superconducting carbon black has higher conductivity than ordinary carbon black, has higher chemical activity, and better dispersion performance.
[0095] In a fourth aspect, an embodiment of the present application further provides a battery, comprising the negative electrode sheet as described above.
[0096] The battery provided in the embodiment of the present application has all the advantages of the positive electrode sheet, which will not be described in detail here.
[0097] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.
[0098] Example 1
[0099] Preparation of conductive adhesive:
[0100] (1) in a protective atmosphere, mixing acrylic acid and deionized water at a temperature of 30° C. to 40° C. to obtain an acrylic acid solution; wherein the mass percentage of the acrylic acid in the acrylic acid solution is 10;
[0101] (2) adding ammonium persulfate and tetramethyl diethylamine to the acrylic acid solution to obtain a first mixed solution, and subjecting the first mixed solution to a polymerization reaction for 25 hours to obtain a polyacrylic acid solution; wherein the mass ratio of acrylic acid, ammonium persulfate and tetramethyl diethylamine in the first mixed solution is 110:1.1:1;
[0102] (3) adding a 1 mol / L sodium hydroxide solution to the polyacrylic acid solution, and then adding aniline and a 1 mol / L ammonium persulfate solution at 3° C. to obtain a second mixed solution, and reacting the second mixed solution at 3° C. for 8 hours to obtain a copolymer solution; wherein the molar ratio of aniline to ammonium persulfate is 1:1, and the molar ratio of sodium hydroxide to acrylic acid is 0.3:1;
[0103] (4) Drying the copolymer solution to obtain a conductive adhesive.
[0104] During the preparation process, by adjusting the ratio of aniline to acrylic acid, a first conductive adhesive having a molar ratio of polyaniline units to polyacrylic acid units of 0.5 and a second conductive adhesive having a molar ratio of polyaniline units to polyacrylic acid units of 1 were prepared respectively;
[0105] Preparation of the battery:
[0106] (1) preparing a positive electrode slurry, wherein the mass proportions of lithium manganese iron phosphate, superconducting carbon black, carbon nanotubes, polyvinylidene fluoride, dispersant and carbon fiber in the positive electrode slurry are 96.9%, 0.5%, 0.4%, 1.8%, 0.2% and 0.2% respectively;
[0107] (2) The positive electrode slurry is coated on both sides of an aluminum foil with a thickness of 12 μm, and after drying, a positive electrode sheet is obtained; wherein the compaction density of the positive electrode sheet is 2.55 g / cm 3 , surface density is 200g / m 2 ;
[0108] (3) preparing a first negative electrode slurry and a second negative electrode slurry, wherein the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the first conductive adhesive in the first negative electrode slurry are 96.0%, 0.8%, 1.2% and 1.5%, respectively, and the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the second conductive adhesive in the second negative electrode slurry are 97.4%, 0.4%, 1.2% and 1.5%, respectively;
[0109] (4) The first negative electrode slurry is coated on both sides of a copper foil with a thickness of 5 μm. After drying, a first active layer is formed on both sides of the copper foil. Then, the second negative electrode slurry is coated on the first active layer to form a second active layer on the first active layer to obtain a negative electrode sheet. The compaction density of the negative electrode sheet is 1.65 g / cm 3 , surface density is 97g / m 2 ;
[0110] (5) preparing an electrolyte by mixing a solvent and a lithium salt; wherein the mass proportions of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in the solvent are 30%, 5%, 25% and 20% respectively, the concentration of the lithium salt is 1 mol / L, and the molar ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is 1:1;
[0111] (6) Assembling a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator into a battery; wherein the electrolyte injection coefficient is 3.1, and the separator adopts a 7μm+2μm+2μm mixed coating separator, that is, the base film thickness is 7μm, and the double-sided coating is 2μm.
[0112] Example 2
[0113] The difference between this embodiment and embodiment 1 is that: in the positive electrode slurry, the mass proportions of lithium iron phosphate, superconducting carbon black, carbon nanotubes, polyvinylidene fluoride, dispersant and carbon fiber are 97.1%, 0.5%, 0.4%, 1.8%, 0.2% and 0.2% respectively; in the first active layer, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the first conductive adhesive are 96.7%, 0.6%, 1.2% and 1.5% respectively; in the second negative electrode slurry, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the second conductive adhesive are 96.7%, 0.6%, 1.2% and 1.5% respectively; the other conditions are consistent with embodiment 1.
[0114] Example 3
[0115] The difference between this embodiment and embodiment 1 is that in the first active layer, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the first conductive adhesive are 97.4%, 0.4%, 1.2% and 1.0% respectively; in the second negative electrode slurry, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the second conductive adhesive are 96.0%, 0.8%, 1.2% and 2.0% respectively; the other conditions are consistent with embodiment 1.
[0116] Example 4
[0117] The difference between this embodiment and embodiment 2 is that in the first active layer, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the first conductive adhesive are 97.4%, 0.4%, 1.2% and 1.0% respectively; in the second negative electrode slurry, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the second conductive adhesive are 96.0%, 0.8%, 1.2% and 2.0% respectively; the other conditions are consistent with embodiment 2.
[0118] Example 5
[0119] The difference between this embodiment and embodiment 1 is that: the molar ratio of polyaniline unit to polyacrylic acid unit in the first conductive adhesive is 0.8; the negative electrode sheet adopts a single-layer coating method, and only the first active layer is coated; in the first active layer, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the first conductive adhesive are 96.7%, 0.6%, 1.2% and 1.5%, respectively; the other conditions are consistent with embodiment 1.
[0120] Example 6
[0121] The difference between this embodiment and embodiment 2 is that: the molar ratio of polyaniline unit to polyacrylic acid unit in the first conductive adhesive is 0.8; the negative electrode sheet adopts a single-layer coating method, and only the first active layer is coated; in the first active layer, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and the first conductive adhesive are 96.7%, 0.6%, 1.2% and 1.5%, respectively; the other conditions are consistent with embodiment 2.
[0122] Example 7
[0123] The difference between this embodiment and embodiment 1 is that the molar ratio of the polyaniline unit to the polyacrylic acid unit in the first conductive adhesive is 1, and the molar ratio of the polyaniline unit to the polyacrylic acid unit in the second conductive adhesive is 0.25; the other conditions are consistent with those in embodiment 1.
[0124] Comparative Example 1
[0125] The difference between this embodiment and embodiment 1 is that: the negative electrode sheet adopts a single-layer coating method, and only the first active layer is coated; in the first active layer, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and polyacrylic acid are 96.7%, 0.6%, 1.2% and 1.5% respectively; the other conditions are consistent with embodiment 1.
[0126] Comparative Example 2
[0127] The difference between this embodiment and embodiment 2 is that: the negative electrode sheet adopts a single-layer coating method, and only the first active layer is coated; in the first active layer, the mass proportions of graphite, superconducting carbon black, sodium carboxymethyl cellulose and polyacrylic acid are 96.7%, 0.6%, 1.2% and 1.5% respectively; the other conditions are consistent with embodiment 2.
[0128] Comparative Example 3
[0129] The difference between this embodiment and embodiment 1 is that the negative electrode sheet adopts a double-layer coating method, wherein the first conductive adhesive and the second conductive adhesive are replaced by polyacrylic acid; the other conditions remain the same as those in embodiment 1.
[0130] The batteries in Examples 1-7 and Comparative Examples 1-3 were subjected to cycle tests and DCR (battery DC internal resistance) tests. The cycle test method is as follows: the battery is fully charged and discharged at 25°C, and the capacity retention rate is recorded after 500, 1000 and 3000 cycles. The DCR test method is as follows: the battery is fully charged at 25°C, and the battery is fully discharged after 0.5h, and the discharge capacity Q is recorded. The battery is fully charged again, and after 0.5h, it is discharged at 0.1C for 0.5Q, and then left for 1h. The voltage at this time is recorded as V0, and then it is discharged at 1C for 30s, and the voltage V1 and current I at the end of the discharge are recorded. Then DCR = (V0-V1) / I, and the unit is converted to mΩ. Among them, full discharge means: at 25℃, discharge at 1C to 2.5V, full charge means: at 25℃, charge at 0.33C constant current to the cut-off voltage (3.65V for LFP battery, 4.2V for LMFP battery), change to constant voltage charging, cut-off current is 0.05C. The test results are shown in Table 1:
[0131] Table 1 Comparison of test results of different embodiments and comparative examples
[0132]
[0133] As can be seen from Table 1, the batteries in Examples 1-7 use the conductive adhesive provided in the examples of the present application, and have better cycle performance and lower DCR than the batteries in Comparative Examples 1-3. Among them, in the batteries of Examples 1-4, the negative electrode sheet adopts a double-layer coating form, which has better cycle performance and lower DCR than the single-layer coating form adopted in Examples 5-6. In Example 7, due to the low content of the conductive agent in the second active layer and the use of a second conductive adhesive with a low molar ratio of polyaniline units to polyacrylic acid units, the conductive performance of the second active layer in the negative electrode sheet is poor, and the improvement in the guiding performance and DCR is not obvious compared with Comparative Examples 1-3.
[0134] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A conductive adhesive, characterized in that: The structural formula of the conductive adhesive is shown in formula (1): Among them, m:n=(1-4):
1.
2. The conductive adhesive according to claim 1, wherein: The molecular weight of the conductive adhesive is 0.9×10 6 -1.5×10 6 .
3. A method for preparing a conductive adhesive, for preparing the conductive adhesive as claimed in claim 1 or 2, characterized in that: include: copolymerizing acrylic acid and aniline to obtain the conductive adhesive; Wherein, the molar ratio of acrylic acid to aniline is (1-4):
1.
4. The method for preparing a conductive adhesive according to claim 3, characterized in that: include: dispersing acrylic acid in a first solvent to obtain an acrylic acid solution; adding a first polymerization agent to the acrylic acid solution to obtain a first mixed solution, and subjecting the first mixed solution to a polymerization reaction to obtain a polyacrylic acid solution; adding sodium hydroxide solution to the polyacrylic acid solution, and then adding aniline and a second polymerization agent to obtain a second mixed solution, and subjecting the second mixed solution to a polymerization reaction to obtain a copolymer solution; The copolymer solution is dried to obtain a conductive adhesive.
5. The method for preparing a conductive adhesive according to claim 4, characterized in that: The step of dispersing acrylic acid into a first solvent to obtain an acrylic acid solution comprises: Under a protective atmosphere, mixing the acrylic acid with deionized water at a temperature of 30° C. to 40° C. to obtain the acrylic acid solution; Wherein, the mass percentage of acrylic acid in the acrylic acid solution is 10%-15%.
6. The method for preparing a conductive adhesive according to claim 4, characterized in that: The step of adding a first polymerization agent to the acrylic acid solution to obtain a first mixed solution comprises: adding ammonium persulfate and tetramethyldiethylamine to the acrylic acid solution to obtain the first mixed solution; Wherein, in the first mixed solution, the mass ratio of acrylic acid, ammonium persulfate and tetramethyldiethylamine is (100-120):(1-1.2):(0.5-1.5).
7. The method for preparing a conductive adhesive according to claim 4, characterized in that: The step of adding sodium hydroxide solution to the polyacrylic acid solution, and then adding aniline and a second polymerization agent to obtain a second mixed solution, and subjecting the second mixed solution to a polymerization reaction comprises: Adding sodium hydroxide solution to the polyacrylic acid solution, and then adding aniline and ammonium persulfate at 0° C.-5° C.; The second mixed solution is reacted at a temperature of 0°C-5°C for 5h-12h.
8. The method for preparing a conductive adhesive according to any one of claims 4 to 7, characterized in that: The molar ratio of aniline to the second polymerization agent is (0.5-2):1; And / or, the molar ratio of sodium hydroxide to acrylic acid is (0.2-0.5):
1.
9. A negative electrode sheet, characterized in that: The invention comprises a current collector and a negative electrode active layer formed on at least one side of the current collector, wherein the negative electrode active layer comprises a negative electrode active material, a conductive agent and a binder; Wherein, the adhesive includes the conductive adhesive as described in claim 1 or 2, and / or the conductive adhesive prepared by the method for preparing the conductive adhesive as described in any one of claims 3-8.
10. The negative electrode sheet according to claim 9, characterized in that: The negative electrode active layer includes a first active layer and a second active layer, the first active layer is arranged on at least one side of the current collector, the second active layer is arranged on a side of the first active layer away from the current collector, the first active layer includes the conductive adhesive, and the second active layer includes the conductive adhesive; The mass proportion of the conductive agent in the first active layer is a1, the mass proportion of the conductive agent in the second active layer is a2, and a1>a2; Wherein, in the conductive adhesive in the first active layer, n / m=b1, and in the conductive adhesive in the second active layer, n / m=b2, and b1<b2.
11. The negative electrode sheet according to claim 10, characterized in that: 0.4%≤a1≤0.6%; and / or, 0.2%≤a2≤0.
4.
12. The negative electrode sheet according to claim 10, characterized in that: 0.25≤b1≤0.5; and / or, 0.7≤b2≤1.
13. A battery, characterized in that: Comprising the negative electrode sheet as described in any one of claims 9 to 12.
Citation Information
Cited By
Conductive adhesive and preparation method therefor, negative electrode sheet, and battery
EP4782470A1
Conductive adhesive and preparation method therefor, negative electrode sheet, and battery
WO2026123479A1